The prescription of disciplinary violations in the Civil Service Law: The problems of its computation and configuration - Boyer Carrera, Janeyri (2020)
The present paper treats about the juridical nature of prescription in administrative sanctioning law and the treatment that it receives in the composition of administrative liability of civil servants. In this context, the paper proposes a typology of prescription period of the administrative disciplinary procedure of the Civil Service Law, analyzing the main issues that each of them present, and makes some proposals of normative improvement that allows these periods to be protective for accused servants and also for Public administration.